Impact of macroeconomic factors towards Malaysian exchange rate / Siti Azilah Mohd Hanafi - Mohd Hanafi, Siti Azilah (Faculty of Business Management, 2017)
This project paper is carried out to providing better understanding for the readers regarding the correlation of macroeconomic factors and exchange rate in Malaysia. The United States is taken as the base country. The variable that be involved under this research is the dependent variable is the exchange rate and the independent variable which are gross domestic product (GDP), money supply, inflation rate and interest rate of Malaysia. The study period for this study is from 1984 until 2015 and the data were collected yearly for 32 years. This research is conducted by using time series data. The method used for this research is Unit root test to see whether the data is stationary or vice versa. There are also Regression Analysis, Correlation Analysis and Descriptive Analysis. Furthermore, the are other test involved which are Normality test, Auto correlation Test, Heteroscedasticity Test, Multicollinearity Test and RAMSEY Reset Test. The test will be done between dependent and independent variable.